Processing of zero load in weight airdynamic experiment on scale 6KETB in wind tunnel ТАД-2 - Виноградський, П. М.; Жданов, О. І.; Лазнюк, П. С.; Павловський P. M. (Proceedings of National Aviation University (archive), 1999)
Proposed is a method of zero load approximation on scale 6KETB in wind tunnel ТАД-2 of Kyiv International University of Civil Aviation which guarantees the increase of operation efficiency of the airdynamic experiment and reduction of experiment time by 30-50 %. Considered is the load hysteresis due to angle change of placing the object of investigation. It is proved that its influence on the measurement error can be neglected